The LEGAL INSTITUTE OF JUDICIAL-PROSECUTION PRACTICE: AN ACCUSED ACCOMPLICE AS A FACTOR IN INCITING YOUTH TO ORGANIZED CRIME - Миленовић, Хаџи Живорад (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
Summary: This paper analyzed the legal institute of judicial-prosecution practice an accused accomplice as a potential factor in inciting young individuals to organized crime. In organized crime, law enforcement agencies instead of individuals deal with a well-structured organization with a solid internal hierarchy, discipline, high level of conspiracy, elaborated strategy, and tactics of concealing criminal activities and evading criminal responsibility. A legal establishment known as "accused accomplice" has been established into Serbian judicial-prosecution system in an effort to identify members of criminal organizations, their associates, and organizers. It's possible that at some point, given the advantages promised to alleged accomplices, youth involvement in organized crime would be encouraged.The research's goal is to determine how students perceive the accused accomplice legal institute as a possible inducement for young people to join organized crime. It is assumed that teenage involvement in organized crime may be encouraged by the rewards promised to members of these organizations for cooperation with the law enforcement. A study was carried out in March 2023 on a sample of 96 high school students, as described in this report, to ascertain this. All research hypotheses were supported by the data obtained using the Scaler - LIJPP - AA - PFIIYTOC (α = .762) and examined using descriptive statistics, factor analysis, and analysis of variance.The importance of the analyzed legal institution in the struggle against corruption, terrorism, and organized crime cannot be denied. As a result, it is widespread throughout the world. On the other hand, if there are findings indicating the researched legal institute has a negative impact on the upbringing of children and youth, the question of whether there is room for its existence emerges. By reassessing or implementing the accused accomplice legal institute in a way that won't adversely effect children's and youths' upbringing, a compromise solution must be sought.
Keywords: plea deal, judicial-prosecution procedures, upbringing, disciplinary measures, and celebrity cult